El Paseo del Río San Francisco: urban development and social justice in Puebla, Mexico - Churchill, Nancy E. (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer outlines a successful ideological war using the discourse of social justice that was employed by the residents of El Paseo del Río San Francisco in Puebla, Mexico, against a government-imposed urban development. She details the four distinct lines of contention in the barrio residents' resistance to the Paseo project—first, the residents formed an alternative discourse on the nature of social justice; second, they challenged the discourse of public utility; third, they constructed an inclusive discourse on the essence of democratic process; and fourth, they rejected the government's claims of just compensation. She presents the testimony of a witness to the finale of the campaign. She concludes that the government turned to the use of force because it had no response to the claims of injustice.